A review of groundwater quality for domestic consumers’ consumption in Perlis / Ahmad Kamal Md Issa - Md Issa, Ahmad Kamal; Badrealam, Sabariah; Elyza Muha, Nor Shafa; Arshad, Mohammad Khairri; Martin, Juliana; Asfar, Juwita; Muhammad, Nur Shazwani; Mohamad Ibrahim, Norlia (Universiti Teknologi MARA, Perlis, 2012)
Towards the 21st century, domestic consumer water demand has kept increasing from time to time. Groundwater may be an alternative source to fulfil this demand especially at the dry areas such as in Perlis. To serve the consumer demand using groundwater, the quality of the groundwater is a major factor to be considered as its contamination may be harmful to human health. In this study the quality of the groundwater currently abstracted from four different geological formations in Perlis which are the Chuping Limestone formation, Setul Limestone formation, Tertiary Bukit Arang formation and Kubang Pasu-Singa formation, are measured using onsite and laboratory tests techniques. From the tests carried on these samples, the groundwater quality is found differed with each other where iron, hardness, copper, chloride and COD concentrations were found high at certain locations. While several parameters were found to exceed the Malaysian Drinking Water Quality Standard. At all locations the groundwater contained total coliform and faecal coliform count. Water treatment methods have been proposed to ensure the groundwater is safe for consumer consumption especially regarding to human health concerns.